The effects of task difficulty on gaze behaviour during landing with visual flight rules in low-time pilots - Naila Ayala; Abdullah Zafar; Suzanne Kearns; Elizabeth Irving; Shi Cao; Ewa Niechwiej-Szwedo (Bern Open Publishing, 2023)
Eye movements have been used to examine the cognitive function of pilots and understand how information processing abilities impact performance. Traditional and advanced measures of gaze behaviour effectively reflect changes in cognitive load, situational awareness, and expert-novice differences. However, the extent to which gaze behaviour changes during the early stages of skill development has yet to be addressed. The current study investigated the impact of task difficulty on gaze behaviour in low-time pilots (N=18) while they completed simulated landing scenarios. An increase in task difficulty resulted in longer fixation of the runway, and a reduction in the stationary gaze entropy (gaze dispersion) and gaze transition entropy (sequence complexity). These findings suggest that pilots' gaze became less complex and more focused on fewer areas of interest when task difficulty increased. Additionally, a novel approach to identify and track instances when pilots restrict their attention outside the cockpit (i.e., gaze tunneling) was explored and shown to be sensitive to changes in task difficulty. Altogether, the gaze-related metrics used in the present study provide valuable information for assessing pilots gaze behaviour and help further understand how gaze contributes to better performance in low-time pilots.